2014
DOI: 10.1136/bmjopen-2014-004988
|View full text |Cite
|
Sign up to set email alerts
|

Higher risk of incident hepatitis C virus among young women who inject drugs compared with young men in association with sexual relationships: a prospective analysis from the UFO Study cohort

Abstract: BackgroundFemale injection drug users (IDUs) may report differences in injection behaviours that put them at greater risk for hepatitis C virus (HCV). Few studies have examined these in association with HCV incidence.MethodsLongitudinal data from a cohort of 417 HCV-uninfected IDU aged 30 or younger were analysed. Cox proportional hazards was used to model female sex as a predictor of new HCV infection. General estimating equation (GEE) analysis was used to model female sex as a predictor of HCV-associated ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 34 publications
3
40
0
Order By: Relevance
“…A number of studies conducted among young PWID have reported female gender as an independent predictor of exposure to HIV and/or HCV 2224 . Prospective cohort studies that have included recruitment of young WWID have documented HIV incidence of 5.3 per 100 person years (PY) 25 and high HCV incidence in the 35–42 per 100 PY range 26,27 among this population.…”
Section: Hiv and Hepatitis C Virus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies conducted among young PWID have reported female gender as an independent predictor of exposure to HIV and/or HCV 2224 . Prospective cohort studies that have included recruitment of young WWID have documented HIV incidence of 5.3 per 100 person years (PY) 25 and high HCV incidence in the 35–42 per 100 PY range 26,27 among this population.…”
Section: Hiv and Hepatitis C Virus Infectionmentioning
confidence: 99%
“…WWID are more likely to have a sexual partner who injects drugs, more likely to be initiated into injection drug use by male sex partners and more likely to be injected by others, including male partners 20,28 . Further, women whose injecting partner is also a sexual partner have an elevated risk of incident HCV infection compared to women and men without overlapping partnerships 24,29 .…”
Section: Hiv and Hepatitis C Virus Infectionmentioning
confidence: 99%
“…Young women who inject drugs (WWID) experience higher rates of both HIV and hepatitis C virus (HCV) infection compared to their male counterparts (Des Jarlais, Feelemyer, Modi, Arasteh, & Hagan, 2012; Esmaeili et al, 2017; Miller et al, 2002; Tracy et al, 2014). Compared to men, WWID are more likely to have overlapping sexual and drug use networks, thus placing the mat higher risk for sexually transmitted and blood-transmitted infections (Bourgois, Prince, & Moss, 2004; Latkin, Forman, Knowlton, & Sherman, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…WWID are also more likely to have a sexual partner who injects drugs and more often report being injected by their partner compared to men who inject drugs (Choi, Cheung, & Chen, 2006; Evans et al, 2003; Frajzyngier, Neaigus, Gyarmathy, Miller, & Friedman, 2007; Montgomery et al, 2002). Additionally, WWID in close relationships, such as sexual relationship or who live with their injecting partner are at greater risk for risky injecting behaviors and experience higher incidence of hepatitis C virus than those not in close injecting relationships (Morris et al, 2014; Tracy et al, 2014). Ethnographic reports of victimization, marginalization, and resource scarcity demonstrate the “everyday violence” WWID experience resulting in high vulnerability to HIV and HCV in young WWID (Scheper-Hughes & Bourgois, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…WWID report higher rates than men for both injecting and sexual HIV risk behaviors (1012). Thus, the risk of infection with blood-borne viruses including HIV and HCV is likely increased among WWID (1, 12, 44). …”
Section: Introductionmentioning
confidence: 99%